Using TMS-EEG to assess the effects of neuromodulation techniques: a narrative review - Cruciani, Alessandro; Mancuso, Marco; Sveva, Valerio; Maccarrone, Davide; Todisco, Antonio; Motolese, Francesco; Santoro, Francesca; Pilato, Fabio; Spampinato, Danny Adrian; Rocchi, Lorenzo; Di Lazzaro, Vincenzo; Capone, Fioravante (Frontiers in Human Neuroscience, 2023)
Over the past decades, among all the non-invasive brain stimulation (NIBS) techniques, those aiming for neuromodulatory protocols have gained special attention. The traditional neurophysiological outcome to estimate the neuromodulatory effect is the motor evoked potential (MEP), the impact of NIBS techniques is commonly estimated as the change in MEP amplitude. This approach has several limitations: first, the use of MEP limits the evaluation of stimulation to the motor cortex excluding all the other brain areas. Second, MEP is an indirect measure of brain activity and is influenced by several factors. To overcome these limitations several studies have used new outcomes to measure brain changes after neuromodulation techniques with the concurrent use of transcranial magnetic stimulation (TMS) and electroencephalogram (EEG). In the present review, we examine studies that use TMS-EEG before and after a single session of neuromodulatory TMS. Then, we focused our literature research on the description of the different metrics derived from TMS-EEG to measure the effect of neuromodulation.